Capital Flight Dynamics: A Comparative Analysis of Determinants in the Indian and Brazilian Economies - Tejwani, Sejal; Sharma, Jaishree; Dinesh, Sharma Ajay (South India Journal of Social Sciences, 2025)
This paper aims to inquire into the determinants of capital flight in India and Brazil using the Autoregressive Distributed Lag estimation technique and bounds testing procedures to demonstrate a long-term equilibrium relationship between Capital Flight and Real Effective Exchange Rate, Rate of Inflation, Stock market, GDP growth rate, and Foreign Direct Investment. The study utilizes yearly data from 1990 to 2023. The bounds test results confirm the existence of cointegration for both India and Brazil. More specifically, in the case of India variables such as GDP growth rate and Real Effective Exchange Rate have had a notable impact on this capital flight in the short-run, while the stock market has a long-run effect. In Brazil, the inflation rate, GDP in the short term, and the stock market in the long term are significant determinants. The diagnostics and stability tests confirm the reliability and stability of coefficients for both nations. Our findings suggest that both nations should focus on strong macroeconomic policies that decrease capital flight and ensure investor stability in their race to become the topmost emerging nations.